Evaluation of Wi-Fi performance in UiTM Jasin for online meeting - Nasrudin, Prity Shahkira; Abdul Halim, Syafnidar; Abu Othman, Noor Ashitah (College of Computing, Informatics, and Mathematics, 2025)
Stable network performance is critical in educational institutions, particularly with the increasing adoption of online meetings for academic purposes. This study investigates the Wi-Fi performance at UiTM Jasin Residential College by analysing throughput, latency, and packet loss during Microsoft Teams sessions. Three experimental configurations were evaluated: (1) same distribution switch, (2) different distribution switches, and (3) multiple different distribution switches. Two laptops acted as clients and a tablet served as the host, while Wireshark was employed for real-time traffic capture. The same distribution switch setup achieved the lowest packet loss (0.009%) but exhibited low throughput (0.525 Mbps) and high latency (7.76 ms). The different distribution switches configuration provided balanced results, with higher throughput (0.763 Mbps) and reasonable latency (7.04 ms), though Laptop A recorded the highest latency (8.86 ms). The multiple distribution switches setup produced inconsistent performance, with Laptop B showing moderate throughput (0.633 Mbps) and latency (7.49 ms), while Laptop A recorded the highest packet loss (0.094%). Overall, packet loss remained low but increased with multiple switches or under congestion. The findings offer insights into network behaviour during peak usage and suggest potential WiFi infrastructure optimizations to enhance the quality of online learning experiences.